A formação do leitor em cenário escolar intercultural de fronteira. - Glasser, Adriane Elisa (2012)
Thinking of the geographic reality of Foz do Iguaçu, space of several ethnic acquaintanceship, cultures and languages, we realize that this multilingual / multicultural reality must be considered when working with teaching of mother tongue. This essay aims to analyse a teaching context of Portuguese language, specifically literature classes, checking the development of these classes, observing how the social agents involved interpret the actions carried out there and how the reader formation happens in this context. For this we well be going back and forward to the theoretical foundation, whenever we deem is necessary, to realize how these participants are evolved in the construction of social reality through the language. We will analyze the interation teacher-student, and, especially, we will investigate how the reader formation happens in this multilingual and multicultural context. These points shows the relevance of these research within the language and society. Because we are worried with the process in wich the social agents are inserted, we can say our research is qualitative, also ethnographic, once it will be developed in a natural environment, besides, is interpretive nature because we worry about to read the teaching learning context. The main estrategies adopted Will be the classes audio recording and video and the developing of field diaries. We will analyse the data collected based on theoretical assumptions of Kleiman (1992, 1993, 1998 e 2004), Smith (1999), Martins (1994), Fairclough (2001), Moita Lopes(1998), Pires-Santos (2004), Vygotsky (2002), Zilberman (2001), Silverman (2009) e Silva (2009), among others. The result expected with this research is the interpretation of Portuguese language teaching context understanding how the reader formation happens in this context.